Comparison of intermittent audit vs daily documentation of pharmacist interventions. (4th December 2020) - Turton, Hannah; Jones, Ceridwen; Levy, Russell; Patanwala, Asad E
Abstract: Purpose: To compare an intermittent audit method vs a daily documentation method with regard to the number of interventions documented by clinical pharmacists in the hospital setting. Methods: A 2-phase pre-post cohort study was conducted at an academic hospital to compare numbers and types of pharmacist interventions documented over an 18-month period before implementation of a daily documentation method (the "pre-phase" period) and during the 6 months after implementation (the "post-phase" period). During the pre-phase period (January 2018 to July 2019), pharmacists prospectively documented interventions on specific audit days. The audit days occurred at approximately monthly intervals. During the post-phase period (July 2019 to March 2020) pharmacists used electronic medical record tools to document interventions daily. The primary outcome was the total number of interventions per day. Values for the pre- and post-phase periods were compared using an unpaired Student t test and through interrupted time series analysis. Results: There were a total of 3, 628 interventions (on 14 intermittent audit days) during the pre-phase period and 9, 300 interventions (on 163 continuous days) in the post-phase period. The mean (SD) number of reported interventions per day decreased from 259 (82) in the pre-phase period to 57 (33) in the post-phase period ( P < 0.001). The mean (SD) number of daily reported interventions per pharmacist decreased from 24 (5) in the pre-phase period to 6 (2) in the post-phase period ( P < 0.001). This decrease was consistent with results of the interrupted time series analysis. There was a decrease in reported interventions at the time of implementation (change from most recent audit day, –125 interventions; 95% confidence interval [CI], –187 to –62 interventions; P < 0.001). Similarly, there was a decrease in reported interventions per pharmacist at the time of implementation (change from most recent audit day, –22 [95% CI, –26 to –18] interventions; P < 0.001). Conclusion: A change from intermittent audits to daily documentation of interventions resulted in an approximately 5-fold decrease in the number of interventions recorded by pharmacists.